The Impact of Training and Development on Teacher Performance - Nurul Faudiah; Fadhilah Fadhilah; Fitriana Fitriana; Rosmala Dewi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
Improving teacher performance still needs to continue to be improved, considering that there are still many bad records about teacher performance or uneven teacher performance. One way to improve teacher performance is by providing training and development to them. This research aims to find gaps in previous research and reanalyze them so that several research questions are asked, the first is how does training influence teacher performance? secondly, how development affects teacher performance and the last is how training and development influence teacher performance simultaneously. This research uses quantitative research which obtains data from respondents using a questionnaire that has been tested on an instrument with a 1-5 Likert scale. To test the instrument, use data validity and reliability tests. Meanwhile, the data analysis technique uses the classic assumption test (linearity test, normality test, heteroscedasticity test, and multicollinearity test). The regression test used uses multiple linear regression, F-test, and T-test to test the hypothesis in this research. The test results show that training and development have a significant influence on teacher performance, while development also has a significant influence on teacher performance. Simultaneously, teacher performance is influenced by training and development. An important finding is how important the resignation indicator of the development variable has an active role in influencing teacher performance with indicators of planning, implementation, and learning innovation as well as learning evaluation.